2022
DOI: 10.3390/agriculture12050714
|View full text |Cite
|
Sign up to set email alerts
|

Seed Coating with Trichoderma harzianum T-22 of Italian Durum Wheat Increases Protection against Fusarium culmorum-Induced Crown Rot

Abstract: Changes in root organization and colonization could be relevant for wheat’s (Triticum durum Desf.) response to F. culmorum-induced crown rot disease (FCR). We investigated the biocontrol and biostimulant efficiency of seeds coated with T. harzianum T-22 (T-22) of four tetraploid wheat seedlings (ancient Saragolle Lucana and modern Creso, Simeto, and Ciclope). In an in vitro experiment, T-22 repressed F. culmorum mycelium growth by over 50% due to the probable combination of competition for nutrients, mycoparas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Trichoderma spp. are among the effective bioagents that are available at the commercial level [54][55][56][57][58]. In our previous study [33], T34 was found as an effective bioagent in controlling stripe rust in a diverse wheat panel.…”
Section: Discussionmentioning
confidence: 98%
“…Trichoderma spp. are among the effective bioagents that are available at the commercial level [54][55][56][57][58]. In our previous study [33], T34 was found as an effective bioagent in controlling stripe rust in a diverse wheat panel.…”
Section: Discussionmentioning
confidence: 98%
“…Some have observed reduced germination percentage in seeds pelleted with different bio-based materials under in vitro conditions, while others have observed increased germination rate. For instance, a reduction in germination percentage has been reported for broccoli seeds coated with soy flour, perennial ryegrass seeds coated with soy flour and durum wheat seeds coated with microbial agent (Amirkhani et al, 2016;Qiu et al, 2020;Vitti et al, 2022). In contrast, increased germination has been reported for red clover seeds coated with soy flour, spring wheat, barley and sugar beet seeds coated with fulvic acid film, and sesame and bean seeds coated with chitosan (Qiu et al, 2020; Braziene et al, 2021; Godínez-Garrido et al, 2022).…”
Section: Effects Of Bio-pellets (Hwg Pp and Kb) On Germination Capaci...mentioning
confidence: 99%
“…Moreover, it has an economic benefit and ensures higher workplace safety for farmers [12,13]. Seed dressing is a valid solution not only to face most biotic stresses but also to reduce the negative impact of abiotic stress, such as drought and salinity, through the application of nutrients, microorganisms and phytohormones [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%